A divulgação científica: uma visão do seu público leitor - Gonzales, Maria Iracema (1992)
This dissertation analysed some aspects of the communicative process Science/Society through the view of a sample taken from the public reader of Science. he majority of the group of readers who took part in the study sample reproduced, not only in tis speech but also in the selection of articles, the view of Scientific Divulgation names internalist. This view of Scientific Divulgation is restricted to scientific principles and facts, using descriptive and argumentative rules of scientific pragmatism. The articles concerning Scientific Divulgation have the scientist/researcher as its main source of information. According to the results obtained, it is possible to conclude that for that group of readers, Scientific Divulgation is predominantly characterized as a communicative process which legitimates the practice and the product of Science.